Exploring environmental audit practices in Malaysia [electronic resource] - Nur Ain Ilyani Mohd Zin, 1992-; Dewi Fariha Abdullah, supervisor; Fakulti Pengurusan (2015)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2015